Pengaruh Kompetensi Pedagogik Guru, Sarana Prasaranadan Budaya Sekolah terhadap Mutu Pendidikan di SMPN Perbatasan Aruk, Sajingan Besar - Dela, Rilma Maya; Niron, Maria Dominika (Jurnal Pesona Indonesia, 2024)
National assessment is a new measurement tool that determines the equality of education quality in Indonesia. This study aims to determine the effect of teacher pedagogical competence, facilities and infrastructure, and school culture on the quality of education and the achievement of national assessment results at SMPN Batas Aruk, Sajinga Besar District. This study uses a quantitative approach with a survey research type, and the analysis is carried out statistically. The results of the study show that: (1) teacher pedagogical competence has a positive and significant effect on the quality of education related to the achievement of national assessment results in the literacy and numeracy aspects of 13.8% with a coefficient of 0.383, (2) facilities and infrastructure have a positive and significant effect on the quality of education related to the achievement of national assessment results in the literacy and numeracy aspects of 16.8% with a correlation coefficient of 0.421, (3) school culture has a positive and significant effect on the quality of education related to the achievement of national assessment results in the literacy and numeracy aspects of 15.5% with a correlation coefficient of 0.405, (4) teacher pedagogical competence, facilities and infrastructure, and school culture have a positive and significant effect on the quality of education at SMPN Batas Aruk, Sajingan District related to the achievement of national assessment results in the literacy and numeracy aspects of 25.9% with a correlation coefficient of 0.531. Thus, several of these factors require special attention to improve the quality of rural education as seen from the quality of educational output regarding students' mastery of literacy and numeracy skills.